Mid- and long-term changes in satiety-related hormones, lipid and glucose metabolism, and inflammation after a Mediterranean diet intervention with the goal of losing weight: A randomized, clinical trial - Hernando-Redondo, J; Toloba, A; Benaiges, D; Salas-Salvadó, J; Martínez-Gonzalez, MA; Corella, D; Estruch, R; Tinahones, FJ; Ros, E; Goday, A; Castañer, O; Fitó, M (Frontiers in Nutrition, 2022)
Background: Obesity is characterized by an increase of adipose tissue, already acknowledged as an endocrine tissue organ. A maze of cytokines, hormones, substrates, and products regulate at short and long-term hunger and satiety through signals from the gastrointestinal tract and adipose tissue. Objective: To compare the mid- and long-term effect of two Mediterranean diet (MedD) interventions with the aim of weight loss or not on peripheral satiety-related hormones, weight loss, glucose and lipid metabolism, and pro-inflammatory markers in obese/overweight subjects with metabolic Methods: A randomized lifestyle intervention, with a large cohort of patients presenting metabolic syndrome. Participants were overweight/obese men and women, who at baseline met at least three metabolic syndrome components. Subjects were assigned to two intervention groups: 1) an intensive life-style intervention with an energy-reduced MedD and physical activity promotion (Intervention Group) with the aim of losing weight, and 2) a normocaloric MedD (Control Group). In the subsample of participants from Hospital del Mar Research Institute (Barcelona), we quantified in a subsample at baseline, 6 months, and 1 year the following analytes: glucose, HbA1c, triglycerides, total cholesterol, high-density lipoprotein cholesterol and LDL cholesterol, C-peptide, ghrelin, GLP-1, glucagon, insulin, leptin, PAI-1, resistin and visfatin. Multivariate analysis and linear mixed-effects models were performed to compare changes in risk factors and biomarkers between intervention groups and over time. Results: Compared to participants in the control group, those in the intervention group showed greater improvements in weight and waist circumference, insulin (P<0.001), glucose metabolism-related compounds (P<0.05), triglyceride-related lipid profile (P<0.05), leptin, blood pressure, and pro-inflammatory markers such as PAI-1 (P<0.001) versus the control group at mid- or/and long-term. Those markers, high-sensitivity C reactive protein, resistin, and vifastin also decreased in both intervention groups. Weight change, regardless of the intervention group, was directly related with an increase in HDL cholesterol and a decrease in LDL cholesterol, systolic and diastolic blood pressure, HbA1c, glucagon, and PAI-1 (P<0.05). Conclusion: An intervention with the aim of weight loss using a hypocaloric MedD and physical activity promotion has beneficial effects on adiposity, glucose metabolism, lipid profile, leptin, and pro-inflammatory markers such as PAI-1 at mid- and long-term.